Is Small Scale Desalination Coupled with Renewable Energy a Cost-Effective Solution? - George Kyriakarakos; George Papadakis (Applied Sciences, 2021)
Water and energy are two of the most important inputs for a community to thrive. While water is dominant on earth, only 2.5% of the water is fresh water and over 98% of that water is either ground water or locked up in glaciers and ice caps. Therefore, only about 1.2% of all the freshwater is surface water which is able to meet human needs. About 2 billion people currently do not have sufficient access to fresh water. One of the solutions deployed in the last decades for island and coastal areas has been desalination. Desalination of seawater and brackish groundwater is commercially available and still a fast-advancing technology. The decreasing cost of renewable energy coupled with strategies based on renewables for powering populations without access to electricity and policies for complete decarbonization of the economy such as the European Green Deal make the combination of renewables and desalination a really interesting approach. This paper investigates combinations of small-scale RO desalination systems which are able to produce up to a few thousand m3 of desalinated water per day coupled with photovoltaic (PV) and wind energy systems, both in grid-connected, as well as in autonomous scenarios. The results show that RO desalination coupled with renewables can address cost-effectively the current issues in terms of water scarcity, while minimizing the environmental footprint of the process. In this paper, it has been showcased that desalination powered by renewables can be deployed in practically any location on earth having access to sea or a brackish water source. The results show that even for grid-connected systems it is more cost-effective and profitable to include a renewable energy system to power the plant, apart from the corresponding environmental benefits.